Perpetrators’ Perspectives on Family Violence: An Event Process Model - Stairmand, Meg (Journal of interpersonal violence, 2021)
Offense process models are descriptive theories that provide a temporal outline of an offense—including its cognitive, behavioral, contextual, and motivational components—from a perpetrator’s perspective. Offense process models have been developed for a wide range of criminal offending (e.g., alcohol-impaired driving, child sexual offending, rape, aggravated robbery, homicide), but remain underdeveloped for family violence. The purpose of this study was to develop an offense process model of family violence. We conducted individual semistructured interviews with 27 participants—14 men and 13 women—completing community-based family violence perpetrator treatment programs, and systematically analyzed participants’ narratives of family violence events using grounded theory methods. The resulting event process model of family violence (FVEPM) contains four sections, arranged temporally from the most distal to the most proximal factors in relation to the family violence event: (1) background factors, (2) event build-up, (3) event, and (4) post-event. Each section outlines the cognitive, behavioral, contextual, and motivational factors that contribute to family violence perpetration. The FVEPM is the first attempt to consider whether a single offense process model can account for a broader range of family violence than that used solely by men toward their female intimate partners. Furthermore, the FVEPM highlights the dynamic nature of family violence events (FVEs), and the salient role of situational and interpersonal factors in contributing to family violence perpetration. We argue that the FVEPM has the potential to accommodate a range of types of family violence perpetration, and makes a useful contribution to theory and research on event-based models from a perpetrator perspective.